OsHKT1;5 mediates Na+ exclusion in the vasculature to protect leaf blades and reproductive tissues from salt toxicity in rice. (13th June 2017) - Kobayashi, Natsuko I.; Yamaji, Naoki; Yamamoto, Hiroki; Okubo, Kaoru; Ueno, Hiroki; Costa, Alex; Tanoi, Keitaro; Matsumura, Hideo; Fujii‐Kashino, Miho; Horiuchi, Tomoki; Nayef, Mohammad Al; Shabala, Sergey; et al.
Summary: Salt tolerance quantitative trait loci analysis of rice has revealed that the SKC1 locus, which is involved in a higher K + /Na + ratio in shoots, corresponds to the OsHKT1;5 gene encoding a Na + ‐selective transporter. However, physiological roles of OsHKT1;5 in rice exposed to salt stress remain elusive, and no OsHKT1;5 gene disruption mutants have been characterized to date. In this study, we dissected two independent T‐DNA insertional OsHKT1;5 mutants. Measurements of ion contents in tissues and 22 Na + tracer imaging experiments showed that loss‐of‐function of OsHKT1;5 in salt‐stressed rice roots triggers massive Na + accumulation in shoots. Salt stress‐induced increases in the OsHKT1;5 transcript were observed in roots and basal stems, including basal nodes. Immuno‐staining using an anti‐OsHKT1;5 peptide antibody indicated that OsHKT1;5 is localized in cells adjacent to the xylem in roots. Additionally, direct introduction of 22 Na + tracer to leaf sheaths also demonstrated the involvement of OsHKT1;5 in xylem Na + unloading in leaf sheaths. Furthermore, OsHKT1;5 was indicated to be present in the plasma membrane and found to localize also in the phloem of diffuse vascular bundles in basal nodes. Together with the characteristic 22 Na + allocation in the blade of the developing immature leaf in the mutants, these results suggest a novel function of OsHKT1;5 in mediating Na + exclusion in the phloem to prevent Na + transfer to young leaf blades. Our findings further demonstrate that the function of OsHKT1;5 is crucial over growth stages of rice, including the protection of the next generation seeds as well as of vital leaf blades under salt stress. Significance Statement: OsHKT1;5 has been strongly suggested to exclude Na + from leaves under salt stress in rice. However, the detailed molecular physiological mechanisms have remained elusive and the knock out mutant has not been investigated in cereal crops. The present manuscript provides evidence that the OsHKT1;5‐mediated leaf blade protection is established not only by Na + unloading from the xylem in roots and leaf sheaths, but also by Na + exclusion in the phloem of basal nodes.